Sosialisasi Prenatal Getel Yoga Untuk Optimalisasi Posisi Janin Di Klinik “C” Kota Bengkulu: Socialization of Prenatal Getel Yoga to Optimize Fetal Position at Clinic "C" Bengkulu City - Rossita, Taufianie; Sari, Liya Lugita; Putri, Yesi (Jurnal Abdi Keperawatan dan Kedokteran, 2023)
In Indonesia, yoga is currently one of the most popular sports, not only by the general public but also by pregnant women. Many benefits can be obtained from prenatal yoga, including the mother feels comfortable and relaxed throughout pregnancy and during childbirth, trains the muscles of the pelvic floor and perineum, keeps the muscles of the body relaxed, balanced during childbirth, reduces stress, increases and improves oxygen circulation to the body and fetus. . This study aims to determine Prenatal Getel Yoga for Optimal Positioning of the Fetus at the Story Kita Care Clinic, Bengkulu City. Counseling for pregnant women at the Bengkulu City Care Clinic.. Seeing the condition of the problems at the Bengkulu City Care story clinic, there are still many pregnant women who do not know about Prenatal Getel Yoga for Optimizing Fetal Position. It is for this reason that prompted the author to carry out community service regarding Getel Yoga Prenatal Socialization for Optimizing the Position of the Fetus at the “C”, Bengkulu City.